ENT 530 Social Media Portfolio: Muslimfrendly / Muhammad Sabiq Khan Ibrahim Shah - Ibrahim Shah, Muhammad Sabiq Khan (2021)
Muslimfrendly is a company that sell Muslim product. The main objective of the business to achieve is providing a Muslim product to our customer at the affordable price. This business start at 1 November 2020. The product that are sold are liked by many people because of the cheap and affordable price. This give a good insight for the increase in sales of our product to its customer. In the beginning of the launching the business there are not much demand because of there are no variation of product that the customer can choose. However as the company vary it product option more demand are get from the customer thus increasing our sale. As the business is growing Muslimfrendly a determine in giving our best effort so the business can be expand in other area.